Biochemical and Biological Properties of a Recombinant Tissue-Type Plasminogen Activator Derived from the Rat JMI-229 Cell Line - Lijnen, H R; Webb, P D; Van Hoef, B; Cock, F De; Stassen, J M; Prior, S D; Collen, D (Thrombosis and Haemostasis, 1992)
Recombinant tissue-type plasminogen activator (rt-PA), produced by expression of the genomic t-PA DNA from the JMI-229 cell line, which is of rat origin, in the host cell line, was purified to homogeneity. JMI-229 rt-PA was obtained essentially as a single chain molecule which was quantitatively converted to a two-chain moiety by treatment with plasmin. The plasminogen activating potential of single chain JMI-229 rt-PA was 5-fold lower than that of commercially available human rt-PA (Actilyse®) in the absence of fibrin, but comparable in the presence of fibrin; it showed a concentration-dependent binding to fibrin, with a significantly more pronounced binding than Actilyse® at low fibrin concentration (85 ± 8% versus 20 ± 7% at 0.025 mg/ml fibrin; p = 0.004). In human plasma in the absence of fibrin, the concentrations of both single chain and two-chain JMI-229 rt-PA required to induce 50% fibrinogen degradation in 2 h, were about 15-fold higher than those of Actilyse®. Both single chain and two-chain forms of JMI-229 rt-PA and of Actilyse® induced a similar time- and concentration-dependent lysis of a 125I-fibrin-labeled plasma clot immersed in human plasma, in the absence of significant systemic fibrinolytic activation. Equally effective concentrations (causing 50% clot lysis in 2 h) were 0.11 or 0.10 pg/ml for single chain or two-chain JMI-229 rt-PA, as compared to 0.11 or 0.15 pg/ml for single chain or two-chain Actilyse®. Continuous infusion over 60 min of single chain JMI-229 rt-PA or Actilyse® in hamsters with a 125I-fibrin-labeled pulmonary embolus, revealed a very similar thrombolytic potency (clot lysis versus dose) and specific thrombolytic activity (clot lysis versus steady state plasma antigen level of t-PA). The initial plasma half-life following intravenous bolus injection of 0.10 mg/kg in hamsters was equally short for JMI-229 rt-PA or Actilyse® (1.2 or 1.4 min respectively).It is concluded that JMI-229 rt-PA has a higher fibrin-affinity and a higher fibrin-specificity in human plasma in the absence of fibrin than Actilyse®, but a comparable thrombolytic potency in a hamster pulmonary embolism model.